Developing climate change dimensions in Malaysia through tourists’ perception - Pengiran Bagul, Awangku Hassanal Bahar (2013)
Climate change has long since ceased to be a scientific curiosity and is no longer just one of many environmental and regulatory concerns. It is a growing crisis with economic, health and safety, food production, security and other dimensions. Shifting weather patterns for example, threaten food production through increased unpredictability of precipitation. Rising sea levels contaminate coastal freshwater reserves and increase the risk of catastrophic flooding. Climate change in Malaysia is usually associated with extreme weather and seasonality. Extreme weather variables include temperature, rainfall and to a certain extent, wind. Meanwhile, seasonality is always associated with dry and wet/monsoon season. This paper outlines the research experience that sets out to determine the dimension of climate change in Malaysia based on tourists’ perception. The establishment of these dimensions will provide structured framework for other researches. The exploratory nature of this research and its comprehensiveness employ both qualitative and quantitative techniques. The research suggests that there are five dimensions of climate change, which are humidity, rainfall, sea level, vegetation and activity. The outputs are expected to establish knowledge on how climatic dimensions affected the socio-economy of a country especially in the tourism industry and help policy-makers to strategise future adaptation planning and responding to the potential threats of climate change in order to achieve sustainable development.